REGENERASI BUDAYA KOPI MELALUI PUSAT EDUKASI TERINTEGRASI FUNGSI EKONOMI DI JAKARTA BARAT - Yosephine Ruth Handoko; Mekar Sari Suteja (Jurusan Arsitektur dan Perencanaan, 2026)
The growing coffee culture in urban areas marks a shift in people's lifestyles, making coffee not merely a consumption commodity but also a medium for social interaction, a means of creative expression, and a driver of local economic activity. The growth of coffee shops and community activities enriches urban social spaces. However, this development also increases coffee processing and consumption waste that has not been managed sustainably. The emerging issue is the imbalance between the rapid development of coffee consumption culture and the low ecological awareness of the resulting environmental impact. This study aims to design a coffee education facility through a regenerative architecture approach as an effort to preserve coffee culture in line with the principles of sustainability. The research methods include literature review, field observation, and conceptual analysis. These methods are used to examine the relationship between community consumption behavior, coffee cultural values, and the application of ecological systems in architectural design as a strategy for urban environmental restoration based on collaboration and community participation. The results show that the application of biophilic design principles and regenerative strategies can create an integrated space that encourages social interaction, learning activities, simultaneously increasing environmental awareness, and empowering local coffee communities as drivers of a circular economy. These findings underscore the role of architecture as a medium for the regeneration of sustainable coffee culture as well as a catalyst for collaboration, innovation, and environmental transformation in urban areas to create more resilient and adaptive urban systems. Keywords: biophilic; culture; education; regenerative; waste Abstrak Fenomena tumbuhnya budaya kopi di kawasan perkotaan menandai pergeseran gaya hidup masyarakat yang menjadikan kopi tidak sekadar sebagai komoditas konsumsi, melainkan media interaksi sosial, sarana ekspresi kreativitas, serta penggerak aktivitas ekonomi lokal. Pertumbuhan kedai kopi dan aktivitas komunitas memperkaya ruang sosial perkotaan. Namun, perkembangan ini juga meningkatkan limbah pengolahan dan konsumsi kopi yang belum dikelola secara berkelanjutan. Isu yang muncul adalah ketidakseimbangan antara laju perkembangan budaya konsumsi kopi dengan rendahnya kesadaran ekologis terhadap dampak lingkungan yang dihasilkan. Penelitian ini bertujuan merancang fasilitas edukasi kopi melalui pendekatan arsitektur regeneratif sebagai upaya pelestarian budaya kopi yang selaras dengan prinsip keberlanjutan. Metode penelitian meliputi studi literatur, observasi lapangan, dan analisis konseptual. Metode tersebut digunakan untuk mengkaji keterkaitan perilaku konsumsi masyarakat, nilai budaya kopi, serta penerapan sistem ekologis dalam desain arsitektur sebagai strategi pemulihan lingkungan perkotaan berbasis kolaborasi dan partisipasi masyarakat. Hasil penelitian menunjukkan bahwa penerapan prinsip biophilic design serta strategi regeneratif mampu membentuk ruang terpadu yang mendorong terjadinya interaksi sosial, aktivitas pembelajaran, peningkatan kesadaran lingkungan secara simultan, serta pemberdayaan komunitas kopi lokal sebagai penggerak ekonomi sirkular. Temuan ini menegaskan peran arsitektur sebagai media regenerasi budaya kopi berkelanjutan sekaligus katalis kolaborasi, inovasi, dan transformasi lingkungan di kawasan perkotaan untuk menciptakan sistem kota yang lebih resilien dan adaptif.